Risk Factors Associated with Prevalence of Swollen Head Syndrome (SHS) in Broiler Chickens in Eastern Province - Saudi Arabia - Al-Ankari, Abdul-Rahman S.; Al-Ramadan, M.A.; El-Demerdash, M.M. (International Journal of Poultry Science, 2004)
A case-control study was conducted to identify risk factors associated with prevalence of swollen head syndrome (SHS) in broiler chickens in Eastern Province of Saudi Arabia (EPSA). A total of 200 birds - originated from 25 broiler flocks - confirmed cases and 200 controls were used in this study. Source of all data were the necropsy reports of the diagnostic investigations carried out at the Veterinary Teaching Hospital-King Faisal University, between July 1999 and June 2000 and the corresponding results of serological testing for turkey rhinotracheitis virus (TRTV) antibodies. Furthermore, a questionnaire was developed and used to collect data from 47 broiler farms on putative risk factors hypothesized to be associated with the prevalence of SHS in production farms. Multiple logistic regression was performed to identify factors associated with SHS. Analysis of the data revealed significant association between TRTV antibodies and clinical signs of SHS (Chi2=292.6; P<0.001) was concluded. Meanwhile, farm`s hygiene and stocking density found to be contributed in prevalence of SHS in open and closed housing system (R2= 87.99 and 53.86%, respectively).